Increased dead space in face mask continuous positive airway pressure in neonates. Issue 1 (22nd June 2016) - Hishikawa, Kenji; Fujinaga, Hideshi; Ito, Yushi
Summary: The objectives: Continuous positive airway pressure (CPAP) by face mask is commonly performed in newborn resuscitation. We evaluated the effect of face mask CPAP on system dead space. Working hypothesis: Face mask CPAP increases dead space. Study design: A CPAP model study. Methodology: We estimated the volume of the inner space of the mask. We devised a face mask CPAP model, in which the outlet of the mask was covered with plastic; and three modified face mask CPAP models, in which holes were drilled near to the cushion of the covered face mask to alter the air exit. We passed a continuous flow of 21% oxygen through each model and we controlled the inner pressure to 5 cmH2 O by adjusting the flow‐relief valve. To evaluate the ventilation in the inner space of each model, we measured the oxygen concentration rise time, that is, the time needed for the oxygen concentration of each model to reach 35% after the oxygen concentration of the continuous flow was raised from 21% to 40%. Results: The volume of inner space of the face mask was 38.3 ml. Oxygen concentration rise time in the face mask CPAP model was significantly longer at various continuous flow rates and points of the inner space of the face mask compared with that of the modified face mask CPAP model. Conclusions: Our study indicates that face mask CPAP leads to an increase in dead space and a decrease in ventilation efficiency under certain circumstances.Pediatr Pulmonol. 2017;52:107–111. © 2016 Wiley Periodicals, Inc.